"Quando o tempo dura uma tonelada": memoirs of a disaster (Palíndromo, 2022)
This article analyzes the disaster occurred in Córrego do Feijão (Brumadinho-MG) from the visual work When Time Lasts a Ton, by the artists Bárbara Lissa and Maria Vaz, who compose the duo Paisagens Móveis. Emphasizing the importance of reconstructing the events and traumas of the past so that it is possible to build other futures, the work makes visible, through an experimental photographic process, the ghosts of this place devastated by the mining greed, covered by mud and by an atmosphere taken by the ore dust daily spread by the trains. Through the act of making visible the remains of the event it is possible to have, even if symbolically, a farewell.
Keywords: photography; memory; temporalities; landscape; disaster